2000
DOI: 10.1289/ehp.001081133
|View full text |Cite
|
Sign up to set email alerts
|

Embryotoxicity of the alkylphenol degradation product 4-nonylphenol to the crustacean Daphnia magna.

Abstract: Laboratory studies have suggested that some alkylphenols and pesticides elicit developmental toxicity to crustaceans. The purpose of the present study was to evaluate the possibility that the alkylphenol degradation product 4-nonylphenol is embryotoxic to the crustacean Daphnia magna through its known ability to interfere with the metabolic elimination of testosterone. Direct exposure of maternal daphnids to testosterone caused developmental abnormalities in neonates that consisted of partial arrest of early e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(22 citation statements)
references
References 15 publications
(11 reference statements)
0
21
0
Order By: Relevance
“…In addition, Meregalli et al [38] observed mouthpart defects in Chironomus riparius larvae for exposure concentrations of 100 µg/l. Morphological abnormalities were also reported in other taxa, such as Daphnia magna (Crustacea) for concentrations of 44 µg/l [39]. Moreover, effects on growth and reproduction were observed in Caernorhabditis elegans (Nematoda) for concentration of 40 µg/l [40].…”
Section: Introductionmentioning
confidence: 72%
“…In addition, Meregalli et al [38] observed mouthpart defects in Chironomus riparius larvae for exposure concentrations of 100 µg/l. Morphological abnormalities were also reported in other taxa, such as Daphnia magna (Crustacea) for concentrations of 44 µg/l [39]. Moreover, effects on growth and reproduction were observed in Caernorhabditis elegans (Nematoda) for concentration of 40 µg/l [40].…”
Section: Introductionmentioning
confidence: 72%
“…Moreover, knowing that crustacean reproduction is linked to the molt cycle (Hyne, 2011), disruption in the molting process could also cause disturbances in reproduction as hypothesized by Gismondi and Thomé (2014) in the amphipod, G. pulex. Indeed, it was observed that the anti-ecdysteroidal activity of nonylphenol caused a reduction in fecundity of many insects (LeBlanc et al, 2000).…”
Section: Chlordecone Effects On the 20-he Concentrationmentioning
confidence: 99%
“…Indeed we found that PBO affected mostly embryo viability and hence cumulative fecundity (which in this study refers to alive offspring production) rather than juvenile or adult survival and age at first reproduction. Piperonyl butoxide (PBO) is a cytochrome P450 (CYP) inhibitor (Hardstone et al, 2015) that inhibits steroid hydroxylases in Daphnia (Baldwin and LeBlanc, 1994), and hence is likely to alter the biosynthesis and metabolism of ecdysteroids, which are crucial for embryo development (LeBlanc et al, 2000). This is in line with a previous study that found that effects of PBO on D. magna population growth rate was mostly related to PBO effects on embryo survival and hence on cumulative fecundity.…”
Section: Discussionmentioning
confidence: 99%
“…PBO is a well-known and widely used insecticide synergist, known to inhibit the activity of the insect cytochrome P450 detoxification system (Hardstone et al, 2015). This compound inhibits steroid hydroxylases in daphnids (Baldwin and LeBlanc, 1994), which are necessary for embryo development (LeBlanc et al, 2000). Furthermore, as a broad inhibitor of cytochrome P450 enzymes, this compound can alter metabolic pathways in exposed embryos.…”
Section: Introductionmentioning
confidence: 99%